ANALISIS PENGUKURAN KINERJA PELABUHAN LAUT LEMBAR BERDASARKAN KRITERIA KINERJA PELABUHAN - MUNAH, DORIAH HASIPATUL; SUTEJA, I WAYAN; WARKA, I GEDE PUTU (GANEC SWARA, 2018)
A port is said to have a good level of service if the time required for loading and unloading items is shorter than the schedule given, so as not to disrupt the schedules of other ships that will be anchored. In order to know the service performance of a port, it is necessary to measure all port activities in order to obtain a service product size that is port operational performance, including service and productivity, port utility and operational performance of service.    To measure the value of the indicator, primary data is needed including the time data of the ship begins to enter the port pool until the ship relinquishes the mooring rope from the dock. Other supporting data are obtained from related technical agencies as secondary data. Performance analysis is conducted in accordance with the guidance of the Director General of Sea Transportation Decree, especially the performance criteria for Lembar Sea Port.    From the result of analysis of nine indicator can be concluded that performance of Lembar Sea Port can be categorized quite good from service and productivity side. While from port uttilitis, operational performance of service is still not good